2018
DOI: 10.1038/s41419-018-1126-4
|View full text |Cite
|
Sign up to set email alerts
|

Nimbolide, a neem limonoid inhibits cytoprotective autophagy to activate apoptosis via modulation of the PI3K/Akt/GSK-3β signalling pathway in oral cancer

Abstract: Of late, nimbolide, a limonoid from the neem tree (Azadirachta indica) has gained increasing research attention owing to its potent antiproliferative and apoptosis-inducing effects. The present study was designed to investigate the effect of nimbolide on autophagy and the time point at which the phosphorylation status of GSK-3β and PI3K dictate the choice between autophagy and apoptosis in SCC131 and SCC4 oral cancer cells. Additionally, we analysed changes in the expression of proteins involved in autophagy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 71 publications
(66 reference statements)
2
105
0
Order By: Relevance
“…Cell viability and colony formation assay were performed as described previously 21,22 . Briefly, cells were seeded in 96-well plates (5000 cells/well) and then were subjected to various indicated treatments.…”
Section: Cell Viability and Colony Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell viability and colony formation assay were performed as described previously 21,22 . Briefly, cells were seeded in 96-well plates (5000 cells/well) and then were subjected to various indicated treatments.…”
Section: Cell Viability and Colony Formationmentioning
confidence: 99%
“…Cell apoptosis was measured using an Annexin V-FITC/ PE Apoptosis kit (BD Biosciences, San Jose, USA) according to the manufacturer's instructions 22 . Briefly, cells were plated into a six-well plate (5 × 10 4 cells/well) for 24 h and then subjected to various indicated treatments.…”
Section: Apoptosis Analysismentioning
confidence: 99%
“…phytochemical agents induced cell apoptosis was through reducing autophagy in tumors [43][44][45][46]. As a potential protumor gene, TAF1L may have an important role as a regulator in response to the stresses for the apoptosis of cancer, which functions are similar to TAF1 gene (its homologous family member) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Predominantly, it was demonstrated that 44 was negatively modulating the PI3K/Akt pathway by the increase of phosphorylated glycogen synthase kinase‐3β (p‐GSK‐3β, involved in the regulation of autophagy and apoptosis based on its phosphorylation status). The increased levels of p‐GSK‐3β silenced the preliminary autophagy activating the apoptosis …”
Section: Autophagy Modulators In Oscc and Esccmentioning
confidence: 99%